Effects of inter-electrode gap and discharge voltage on EUV emission from stainless steel vacuum spark plasma - Saboohi, S; Yap, S·L; Chan, L·S; Wong, C·S (Universiti Kebangsaan Malaysia, 2012)
The emission of Extreme Ultra Violet (EUV) from plasma produced by vacuum spark discharge using stainless steel as anode material was investigated. The operating pressure for all the experiments carried out was maintained at below 10-4 mbar. The discharge voltage tested was from 8 kV to 20 kV. The inter-electrode distance suitable for high intensity and reproducible EUV emissions was found to be in the range of 2.6 mm to 4.6 mm. The output EUV energy scaled as ~ V02, where V0 is the discharge voltage.